Students' Mathematical Communication Ability through Blended Learning Model for Elementary School Students in Banda Aceh - Indah Suryawati; Rahmani Rahmani; Nur Ainun (International Conference on Multidisciplinary Research, 2022)
Mathematics is an exact science, mathematics is studied from elementary school to college level. One of the objectives of learning mathematics in the 2013 Ministry of Education and Culture is that students are able to have mathematical communication skills. Because with mathematical communication skills, students can convey their ideas both orally and in writing, so that in the learning process a good understanding can be formed. The purpose of this study is to determine whether using the station rotation type blended learning model can improve students' mathematical communication skills. This study uses a quantitative approach, while the design used in this study is a one group pretest-posttest control design. The sample in this study used purposive sampling technique. Thus, the research sample in this study is class Vc, because class Vc has less ability in mathematics than classes Va and Vb, based on observations from the three homeroom teachers. The data in the study were taken by giving pretest and posttest questions about mathematical communication skills about the material of building space. Furthermore, to determine the increase in mathematical communication skills in this study was carried out using the paired t test formula. The results show that the t-count is 17.02, while the t-table with a significant level of 5% or 0.05 is 2.04, so Ha is accepted and it can be concluded that there is an increase in students' mathematical communication skills who are taught using the learning model. Station rotation type blended learning. Keywords: Mathematical Communication Skills, Blended Learning